The Effect of Self-Regulation on Strategic Thinking Ability - Gunardi, Sukmo; Djuwita, Tita Meirina (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This study aims to analyze the relationship between self-regulation and strategic thinking skills in students, especially in the context of decision-making in a dynamic educational environment. The background of this research departs from the need to understand the psychological factors that influence strategic thinking processes, which are increasingly important in facing complex challenges in various fields, including business and education and to prepare students as future leaders. Self-regulation, which involves an individual's ability to control emotions, behaviours, and thoughts, is believed to play a significant role in shaping effective strategic thinking skills. The research method used was a quantitative method with a sample of 238 respondents consisting of final-year students. The sampling technique was purposive random sampling. The variables involved in this study are self-regulation as an independent variable and strategic thinking ability as a dependent variable. The instrument used is a structured questionnaire that measures the two variables using a 5-point Likert scale. The results showed that there was a significant positive relationship between self-regulation and strategic thinking skills. Individuals with a high level of self-regulation tend to be more able to think strategically, show better analytical skills, and be more adaptive in dealing with changing situations. The development of self-regulation can be a key factor in improving strategic thinking skills, which are relevant in a variety of professional and academic contexts.